Integrated Enterprise Resilience Architecture Framework for Surviving Strategic Disruptions - Hassan Ahmed Hassan Mohamed; Galal Hassan Galal-Edeen (JOIV : International Journal on Informatics Visualization, 2019)
Resilient business enterprises are able to survive strategic disruptions like technology disruptions and come back more successful. They succeed because they develop and effectively implement the resilience strategies of mitigation, adaption, and transformation. This paper proposes an integrated resilience framework that is based on a combination of enterprise architecture and business architecture frameworks. At the core of the proposed framework is a meta-model and a method. The framework guides the development of a unified vision of how a business enterprise can address a specific strategic disruption and transform itself in a successful way. The framework articulates the vision through the lens of business blueprint views that guide the formation of transformation initiatives. Through the mapping capabilities of the framework, the transformation initiatives cross over the boundaries between organization structures and domains. In the last section we demonstrate our proposed method and meta-model with the help of a case study.